Iftar in trays at campus remains in memories - Siti Nur Azwin, Zulkapri (2020)
Kuantan, 30 April 2020 - Universiti Malaysia Pahang (UMP) students were excited when allowed to return to their homes after being stranded on campus for more than 40 days due to the Movement Control Order (MCO) started on 18 March 2020.